NEW APPROACHES TO TEACHING LATIN IN MEDICAL UNIVERSITIES (International journal of medical sciences, 2025)
Latin remains a cornerstone of medical education, providing the etymological foundation for much of the terminology used in anatomy, pharmacology, and clinical practice. However, traditional teaching methods often fail to engage modern students, leading to calls for innovative pedagogical strategies. This literature review examines recent advancements in teaching Latin to medical students, drawing on scholarly sources to analyze approaches such as digital tools, gamification, blended learning, and contextual integration. Through a systematic search of academic databases and journals, key studies were identified that highlight the effectiveness of these methods in improving student motivation, retention, and application of Latin-based terms. Results indicate that incorporating technology and interactive elements significantly enhances learning outcomes compared to rote memorization. The discussion explores implications for curriculum design, emphasizing the need for hybrid models to bridge historical traditions with contemporary educational needs. Overall, these new approaches promise to revitalize Latin instruction, making it more relevant and effective for future healthcare professionals.